Lesions in cattle leather caused by the main ectoparasites in Northwest of Paraná State and Southwest of Mato Grosso state - Marques, Francisco Augusto Carlos; Yamamura, Milton Hissashi; Vidotto, Odilon (Semina: Ciências Agrárias, 2000)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This work evaluates the lesions caused by ectoparasites like Boophilus microplus, Dermatobia hominis, Haematobia irritans in cattle leather, in tanning industry. Such material came from the Northwest of Parana State and Southwest of Mato Grosso State. The evaluation of leather occured in August, 1999 and February, 2000. In August, 1999, 15,530 samples from Northwest of Parana State and 11, 289 samples from the Southwest of Mato Grosso State were analysed. The result obtained showed that the main damage was caused by ticks bites, representing 63% in Parana and 67% in Mato Grosso of cattle leather infected by tick. It was followed by D. hominis (Tropical warble) infection, where 34% of the cattle in Parana and 19% in Mato Grosso showed larvae infection and 3% in Parana and 14%> of the remaining cattle presented lesions by horn fly. In February, 2000 9,690 samples from Northwest of Parana State and 16,271 samples from the Southwest of Mato Grosso State were analyzed. Again the highest incidence of damage was caused by the ticks where 60% of cattle leather in Parana and 65% in Mato Grosso were infected. It was also followed by tropical warble infection, where 35,5% of cattle in Parana and 20% in Mato Grosso presented larvae infection and 4,5% in Parana and 15%> of the remaining cattle showed lesions by horn fly. Although tick caused greater leather lesions, the larvae ofD. hominis was responsible for the low quality of the material because such damage is irreversible. The Parana State obtained the lowest score for leather due to the high incidence of larvae od D. hominis.